2008
DOI: 10.1245/s10434-008-0229-z
|View full text |Cite
|
Sign up to set email alerts
|

Sentinel-Lymph-Node-Based Management or Routine Axillary Clearance? One-Year Outcomes of Sentinel Node Biopsy Versus Axillary Clearance (SNAC): A Randomized Controlled Surgical Trial

Abstract: We sought the extent to which arm morbidity could be reduced by using sentinel-lymph-node-based management in women with clinically node-negative early breast cancer. One thousand eighty-eight women were randomly allocated to sentinel-lymph-node biopsy followed by axillary clearance if the sentinel node was positive or not detected (SNBM) or routine axillary clearance (RAC, sentinel-lymph-node biopsy followed immediately by axillary clearance). Sentinel nodes were located using blue dye, alone or with techneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
144
1
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 198 publications
(151 citation statements)
references
References 17 publications
5
144
1
1
Order By: Relevance
“…Seven trials were thus eligible, as shown in Table 1 [3,4,[7][8][9][10][11]. A total of 9,608 patients were randomly assigned to treatment (658 in the SNB only arm, 5,084 in the ALND only arm and 4,406 who had SNB and then went onto have ALND), and data was available for analysis from 8,853 of them (636, 4,389 and 3,828 in the three arms, respectively).…”
Section: Eligible Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…Seven trials were thus eligible, as shown in Table 1 [3,4,[7][8][9][10][11]. A total of 9,608 patients were randomly assigned to treatment (658 in the SNB only arm, 5,084 in the ALND only arm and 4,406 who had SNB and then went onto have ALND), and data was available for analysis from 8,853 of them (636, 4,389 and 3,828 in the three arms, respectively).…”
Section: Eligible Studiesmentioning
confidence: 99%
“…There was little variability among studies in the menopausal status, eligible stages of breast cancer and tumour size of participants. All seven trials enroled patients between 1998 and 2005, and six of the seven studies were multicentre trials [4,[7][8][9][10][11].…”
Section: Eligible Studiesmentioning
confidence: 99%
See 3 more Smart Citations